P352 Game-It (Games For Improving Treatment-Recommendations). (15th August 2013) - Brandt, L; McCallum, S; Kristiansen, A; Agoritsas, T; Akl, E; Vandvik, P; Montori, V
Abstract : Background: Traditionally patients are not involved in the development of clinical guidelines, and most current panels include only clinical and methodological experts. We therefore know little about what patients (or healthy lay people) would have recommended if they were provided with the same evidence as experts. Objectives: Develop a prototype 'Recommendation-making game' which can be used for: (1) Exploring patients and lay people's reasoning when facing the same evidence as an expert guideline panel; (2) assess whether they give similar value to the outcomes or burdens if the decision of making a recommendation for a patient group was up to them; (3) determine whether their recommendation concur with what they would have decided for themselves. Methods: We used game technology to make a generic prototype of an online "Recommendation-making game", based on structured guidelines published in the MAGIC (Making Grade the Irresistible Choice) application. This approach will enable us to automatically make online surveys out of any guideline/recommendation in the system. In making it into a game we believe people would want to participate, and we can potentially harvest information from a large group of people. The game can also be used in small focus groups for qualitative data collection. Results: We will display the prototype at the conference. Discussion: Does clinical experts reasoning effects that of patient representatives in a guideline panel? Implications for Guideline Developers/Users: GAME-IT explores a new way of harvesting information from patients (or healthy lay people) regarding treatment recommendations.